Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Differential Equations Problem please help?
Use the Laplace Method to solve the equation:
x'' + 2x' + x = e^(t+1)
x(0)=0, x'(0)=0
1 Answer
- RapidfireLv 710 years agoFavorite Answer
I do not know that method, but I am sure it is not the simplest way.
Find the complementary function by solving the auxiliary equation:
x'' + 2x' + x = 0
m² + 2m + 1 = 0
(m + 1)² = 0
m + 1 = 0
m = -1
xᶜ = (At + B)℮⁻ᵗ
Find the particular integral by comparing coefficients:
xᵖ = C℮^(t + 1)
xᵖ' = C℮^(t + 1)
xᵖ'' = C℮^(t + 1)
xᵖ'' + 2xᵖ' + xᵖ = ℮^(t + 1)
C℮^(t + 1) + 2C℮^(t + 1) + C℮^(t + 1) = ℮^(t + 1)
4C℮^(t + 1) = ℮^(t + 1)
4C = 1
C = ¼
xᵖ = ℮^(t + 1) / 4
Find the general solution by combining these two parts:
x = xᶜ + xᵖ
x = (At + B)℮⁻ᵗ + ℮^(t + 1) / 4
x = ℮^(t + 1) / 4 + (At + B)℮⁻ᵗ
Find the particular solution by solving for the constants:
When t = 0, x = 0
℮ / 4 + B = 0
B = -℮ / 4
x' = ℮^(t + 1) / 4 - [At - (A - B)]℮⁻ᵗ
When t = 0, x' = 0
℮ / 4 + A - B = 0
A = B - ℮ / 4
A = -℮ / 4 - ℮ / 4
A = -℮ / 2
x = ℮^(t + 1) / 4 + (-℮t / 2 - ℮ / 4)℮⁻ᵗ
x = ℮^(t + 1) / 4 - (2℮t + ℮)℮⁻ᵗ / 4
x = ℮^(t + 1) / 4 - (2t + 1)℮℮⁻ᵗ / 4
x = ℮^(t + 1) / 4 - (2t + 1)℮^(1 - t) / 4
x = ℮^(t + 1) / 4 - (2t + 1) / [4℮^(t - 1)]